“Treating equally is not always treating fairly”: Migrant students at Swiss Universities of Applied Sciences between experiences of difference and agency - Le Breton, Maritza; Böhnel, Martin (Momentum Quarterly, 2019)
This article is based on a recent Swiss research project on migrant bachelor students at Universities of Applied Sciences and Universities of Education in the German-speaking and French-speaking part of Switzerland, using the educational fields, inter alia, social work and education. Results of the study highlight the complex interplay of gender, migration or national provenience and further dimensions of social differentiation about students’ perception in these fields of education. Starting from an intersectional approach on higher education institutions, this contribution addresses formal/informal factors in the university environment and its impact on male/female students’ perception of difference, belonging and study success. This contribution wants to point out the practices which students develop in dealing with experiences of social inequality.